On the Social Desirability of Patents for Sequential Innovations in a Vertically Differentiated Market - Luca Lambertini; Pietro Tedeschi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We consider a market for vertically differentiated goods where firms enter over time, after having developed innovations characterized by different quality levels. We show that the adaptation of a patent system limiting the quality range available to later entrants is socially undesirable, in that it builds a barrier to entry to the advantage of the first innovators.
Keywords: 330